Peningkatan Kompetensi Disabilitas dalam Pengembangan dan membangun Usaha di Unique Tailor - Wahyuningsih, Susanti; Kurniawati, Endang; Fitriani, Fatma Awalia; Lestari, Adelia Gita; Sidiq, Fajar; Putri, Yunita (STIE Pelita Nusantara, 2024)
In Indonesia, disability is still a matter for individuals who have disabilities. Persons with disabilities are part of Indonesian citizens who have the same rights and obligations as citizens who do not suffer from physical or psychological disabilities. Society still thinks negatively about people with disabilities because of the shortcomings they experience, so that discrimination against people with disabilities arises. Persons with disabilities are seen as unproductive, uncreative and innovative and contribute less to the government in various aspects. The existence of this kind of view can provide limited space for disabled people to participate in various aspects of life, both in spiritual aspects, economic aspects, educational aspects, social aspects and so on. With such an assumption, it requires people with disabilities to be more productive and continue to develop, as well as changing society's thinking which considers them weak. Therefore, our group collaborates with people with disabilities by carrying out embroidery training so that we can show the wider community that people with disabilities can produce work. We believe that good cooperation and communication between our member groups and people with disabilities will produce work that produces useful benefits for the wider community. Keywords: people with disabilities, embroidery training, producing work